Primary Intestinal Hodgkin’s Lymphoma: An Uncommon Presentation - Sharma, Shruti; Rana, Safia; Kapur, Sujala; Jairajpuri, Zeeba Shamim (Journal of Laboratory Physicians, 2013)
Primary intestinal lymphoma is a rare lymphoproliferative neoplasm of the small intestine. The primary nature is established on the basis of lack of evidence of lymphoma on chest X-ray, computerized tomographic scan, peripheral blood or bone marrow puncture. Tumor involvement is limited to the gastrointestinal tract, the criteria for inclusion are that the symptoms related to the small intestine are predominant or the only symptoms at the time of laparotomy. Hodgkin's lymphoma (HL) primarily in the small intestine is a rare entity and an uncommon presentation of the disease. Ileum is the more common site of infliction than the jejunum because of its abundant lymphoid follicles. Here, we present a case of primary intestinal HL, in a 30-year-old male.
Keywords: Hodgkin’s lymphoma; postmortem; small intestine